Potential Effects of MSC-Derived Exosomes in Neuroplasticity in Alzheimer’s Disease - Reza-Zaldivar, Edwin E.; Hernández-Sapiéns, Mercedes A.; Minjarez, Benito; Gutiérrez-Mercado, Yanet K.; Márquez-Aguirre, Ana L.; Canales-Aguirre, Alejandro A. (Frontiers in Cellular Neuroscience, 2018)
Alzheimer's disease (AD) is the most common type of dementia affecting regions of the central nervous system that exhibit synaptic plasticity and are involved in higher brain functions such as learning and memory. AD is characterized by progressive cognitive dysfunction, memory loss, and behavioral disturbances of synaptic plasticity and energy metabolism. Cell therapy has emerged as an alternative treatment of AD. The use of adult stem cells, such as neural stem cells and Mesenchymal Stem Cells (MSCs) from bone marrow and adipose tissue, have the potential to decrease cognitive deficits, possibly by reducing neuronal loss through blocking apoptosis, increasing neurogenesis, synaptogenesis, and angiogenesis. These processes are mediated primarily by the secretion of many growth factors, anti-inflammatory proteins, membrane receptors, microRNAs (miRNA) and exosomes. Exosomes encapsulate and transfer several functional molecules like proteins, lipids, and regulatory RNA which can modify cell metabolism. In the proteomic characterization of the content of MSC-derived exosomes, more than 730 proteins have been identified, some of which are specific cell type markers and others are involved in the regulation of binding and fusion of exosomes with adjacent cells. Furthermore, some factors were found that promote the recruitment, proliferation, and differentiation of other cells like neural stem cells. Moreover, within exosomal cargo, a wide range of miRNAs were found, which can control functions related to neural remodeling as well as angiogenic and neurogenic processes. Taking this into consideration, the use of exosomes could be part of a strategy to promote neuroplasticity, improve cognitive impairment and neural replacement in AD. In this review, we describe how exosomes are involved in AD pathology and discuss the therapeutic potential of MSC-derived exosomes mediated by miRNA and protein cargo.